2009
DOI: 10.1080/13697130902736921
|View full text |Cite
|
Sign up to set email alerts
|

Non-hormonal treatment of hot flushes in breast cancer survivors: gabapentin vs. vitamin E

Abstract: Gabapentin appears to be effective for the treatment of hot flushes with a favorable effect on quality of sleep. Vitamin E has only marginal effect on vasomotor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 13 publications
0
36
0
1
Order By: Relevance
“…Five randomized controlled trials compared a non-pharmacologic with a pharmacologic hot flash treatment in women with breast cancer (Table 1; Supplementary material 2) [25, 3740]. These trials took place in Egypt, Italy, and the United States and were single-center studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five randomized controlled trials compared a non-pharmacologic with a pharmacologic hot flash treatment in women with breast cancer (Table 1; Supplementary material 2) [25, 3740]. These trials took place in Egypt, Italy, and the United States and were single-center studies.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture was compared with gabapentin or venlafaxine in two trials [25, 40]. Gabapentin was compared with vitamin E or hypnosis in two trials [37, 38]. Pregabalin was compared with stellate ganglion block in one study [39].…”
Section: Resultsmentioning
confidence: 99%
“…45 Similarly, studies of vitamin E for HF have not yielded encouraging results. 5,46 Although high vitamin use has been reported in previous studies of cancer population, some authors have suggested possible harm from the use of antioxidants while others indicated that patients derive benefits from such use. 47 The results of this study could be indicative of more women with hot flashes consuming vitamins in expectation of a relief; however, future research should ascertain the potential effects of vitamins on HF.…”
Section: Discussionmentioning
confidence: 99%
“…5 Hormonal treatment is effective in controlling HF; however, hormone replacement therapy is contraindicated in women with breast cancer. 6 Several non-pharmacologic treatments including Complementary and Alternative Medicine (CAM) modalities are commonly used by cancer patients; however, their efficacy is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Enfi n, dans une dernière étude comparant la gabapentine à la vit E (800 UI/j) comme traitement du groupe témoin, un effet très marginal de la vit E sur les bouffées de chaleur est noté avec une fréquence et un score réduit de 10 et de 7 % respectivement [13].…”
Section: Effets De La Vit E Sur Les Bouffées De Chaleur Chez Les Femmunclassified